Hexamerization of Anti-SARS CoV IgG1 Antibodies Improves Neutralization Capacity - Pande, Kalyan; Hollingsworth, Scott A.; Sam, Miranda; Gao, Qinshan; Singh, Sujata; Saha, Anasuya; Vroom, Karin; Ma, Xiaohong Shirley; Brazell, Tres; Gorman, Dan; Chen, Shi-Juan; Raoufi, Fahimeh; et al. (Frontiers in Immunology, 2022)
The SARS-CoV-2 pandemic and particularly the emerging variants have deepened the need for widely available therapeutic options. We have demonstrated that hexamer-enhancing mutations in the Fc region of anti-SARS-CoV IgG antibodies lead to a noticeable improvement in IC50 in both pseudo and live virus neutralization assay compared to parental molecules. We also show that hexamer-enhancing mutants improve C1q binding to target surface. To our knowledge, this is the first time this format has been explored for application in viral neutralization and the studies provide proof-of-concept for the use of hexamer-enhanced IgG1 molecules as potential anti-viral therapeutics.